Individual variation in the compromise between social group membership and exposure to preferred temperatures. Issue 1880 (13th June 2018) - Cooper, B.; Adriaenssens, B.; Killen, S. S.
Abstract : Group living is widespread among animal species, and comes with a number of costs and benefits associated with foraging, predator avoidance and reproduction. It is largely unknown, however, whether individuals sacrifice exposure to their own preferred or optimal environmental conditions so they can remain part of a social group. Here, we demonstrate that individual three-spine sticklebacks vary in the degree to which they forego exposure to their preferred ambient temperature so they can associate with a group of conspecifics. Individual fish varied widely in preferred temperature when tested in isolation. When the same individuals were presented with a choice of a warm or cold thermal regime in the presence of a social group in one of the environments, fish spent more time with the group if it was close to their own individually preferred temperature. When a group was in a relatively cool environment, focal individuals that were more social deviated most strongly from their preferred temperature to associate with the group. Standard and maximum metabolic rate were not related to temperature preference or thermal compromise. However, individuals with a higher standard metabolic rate were less social, and so energetic demand may indirectly influence the environmental costs experienced by group members. The reduced tendency to engage with a social group when there is a large difference between the group temperature and the individual's preferred temperature suggests a role for temperature in group formation and cohesion that is mediated by individual physiology and behaviour. Together, these data highlight exposure to non-preferred temperatures as a potential cost of group membership that probably has important but to date unrecognized implications for metabolic demand, energy allocation, locomotor performance and overall group functioning.